MANUFACTURE OF MALEIC ANHYDRIDE COPOLYMER PARTICLE - MUROI YOSHIYUKI; OTANI SHOJI; FUKUDA MASAHIRO; TSUSHIMA RIKIO (1989)
PURPOSE:To produce the subject particles which are useful as an emulsion stabilizer, a sizing agent for paper, a concrete slump loss inhibitor, etc. easily in a high yield, by subjecting maleic anhydride and a vinyl monomer to radical polymerization in a specific solvent in the presence of a cellulose ester or cellu lose ether. CONSTITUTION:Maleic anhydride (A) and a vinyl monomer (B) copolymerizable with the component (A) selected from the group consisting of 2-22C olefins, styrene monomers, vinyl ethers of 1-22C alkyls, vinyl esters of 2-22C aliphatic carboxylic acids, etc. are subjected to radical copolymerization in a solvent (D) which dissolves the above monomer but does not dissolve the copolymer that will be produced in such an amount that the concentration of the copolymer that will be produced is 5-35wt.% at 30-150 deg.C, with the molar ratio of A to B being 1/2-2/1, in the presence of a cellulose ester or cellulose ether (C) having a weight-average molecular weight (according to GPC) of 1,000-800,000 in an amount of 0.05-20pts.wt. for 100pts.wt. component (A), thereby producing the title particles of which particle distribution is monodisperse and which will not form any aggregate and has a particle diameter of 10mum or below.